A longitudinal study of a lateral intracranial aneurysm: identifying the hemodynamic parameters behind its inception and growth using computational fluid dynamics - Oliveira, I. L. [UNESP]; Santos, G. B. [UNESP]; Militzer, J.; Baccin, C. E.; Tatit, R. T.; Gasche, J. L. [UNESP] (Springer Nature, 2021)
In the last two decades, the application of computational fluid dynamics (CFD) to study the blood flow in intracranial aneurysms has gained popularity since hemodynamics plays a key role in the inception, growth, and rupture of these aneurysms. Although the rupture event has been the main focus of these studies, other researches have shown the importance of hemodynamics also on the initiation and growth of intracranial aneurysms. However, due to the lack of follow up examinations of a single aneurysm case, these studies are scarcer. In this work, two consecutive examinations of an unruptured lateral aneurysm followed up for 5 years were used to investigate the growth of the aneurysm by using CFD. By simulating the flow in these two geometries and in the virtually reconstructed hypothetical healthy vasculature, correlations between hemodynamic parameters and the growth of the aneurysm were evaluated. The results showed that the inception of the aneurysm correlated positively with high wall shear stress (WSS) and high positive WSS spatial gradient, as other studies also suggest. Furthermore, and most importantly, as different biological pathways may explain the influence of hemodynamics on the growth process, the results also pointed out that the hemodynamic effects that drove the subsequent growth of the aneurysm have changed to a combination of low WSS and high oscillatory shear index (OSI). Thus, even though the driving mechanisms observed during each period are distinct, they strongly agree with two main theories that currently explain aneurysm inception and growth.
Keywords: Aneurysm growth; Computational fluid dynamics; Hemodynamics; Intracranial aneurysms